GASIFIKASI SEKAM PADI (BIONER-1) - Sjaffriadi, Sjaffriadi; Nurachman, Budi (Jurnal Energi dan Lingkungan (Enerlink), 2011)
Indonesia has potential abudant biomass wastes. Annual paddy production in Indonesia is approximately 50 million tons, from which 14 tons of rice husks is produced, assuming that each ton paddy could produce 0.28 tons of rice husks. At its calorific value of 12.5 MJ/kg, the annual potential energy provided by these husks is around 175 GJ. A gasification system using rice husk would normally require 1.5 to 2 kg of rice husks to generate 1 kWh of electricity. Therefore, each ton of rice milled could produce wastes that equals to electricity generation of 150 kWh. Rice husk is about 14 to 28.5% of a rice grain, but mostly has an average value of 25%. A gasification Bioner-1 system is operated 14 hours per day in 366 days per year. This system will drive a rice milling unit for 8 hours per day and produce electricity for villagers for another 6 hours in the evening. At a fuel consumption of 25 kg per hour, the system will require 130 tons of husks that will be provided from rice fields of around 175 ha. Gas (syngas) produced from the gasification will be used for a dual fuel diesel engine system, supplementing diesel fuel. The diesel fuel substituted by the gas could reach about 75-80%. At a consumption rate of 25 kg/hour rice husks in the system, the husks consumption per kWh electricity is 1.5 kg (1.5 kg/kWh) and the efficiency of rice husks conversion is 15%. A small portion of tar could still escape from a gas cleaning system. The tar could be observed during overhoul of the diesel engine. The tar entering into the diesel engine is overcome through switching on the diesel engine for about 10 minutes and flushing using diesel oil right before it is shutted down. Through this method, the tar entering the diesel engine is completely burned. Kata kunci gasification, biomas, rice husk, diesel engine